About a uni-cervical unicorn uterus case with vaginal septum - E., Mapatano Shalamba; L., Kalala Kanyinda; M., Kiminyi Kalunga; O., Nyakio Ngeleza; L., Kanku Tudiakwile; D., Mukwege Mukengere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The unicorn uterus is a common uterine malformation after septate uteri, accounting for 30 to 50% of cases. We report a case of unicorn uterus with an associated vaginal septum discovered during the obstetrical examination of a consultant surgeon for hemorrhage, and exploration of the uterus revealed a uterus during a cesarean section. Maternal-fetal rescue for placenta previa. The interest of this case is to show the double embryological mechanism involved, unilateral aplasia of the muller ducts and the lack of resorption explaining this vaginal septum.